The Impact of Assessment on the Motivation Level of the Student:A Study on Middle School Students. - Marya; Khan, Muhammad Asif; Jamshed, Aneela (ACADEMIA International Journal for Social Sciences, 2026)
The present study investigated the impact of assessment on student motivation at the middle level. It aims to explore the motivation level of students by assessing their progress. Combining qualitative and quantitative methods provided a comprehensive analysis of the gathered information in the research design. The mixed-method approach enabled the researchers to provide both qualitative and quantitative explanations of the collected data. The study involved administering student questionnaires and conducting teacher interviews. The questionnaire was administered to grade six, seven, and eight students to evaluate their learning and motivation levels. The study was conducted in the Katlang schools district of Mardan province in KPK, Pakistan. A total of 20 middle schools in Katlang were assessed, and 12 middle schools, including 384 students, were selected for the study. The results indicated a positive correlation between the student's assessment scores and their level of motivation. Additionally, the analysis revealed that teachers' assessment practices significantly impact the student's motivation levels. The study's findings have shown that assessment practices play a crucial role in middle school students' teaching and learning process. Based on the outcomes, it can be concluded that effective assessment practices can highly motivate students and enhance their desire to learn.